2023
DOI: 10.2337/dc22-2426
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing the Efficacy and Safety of IDegLira Versus Basal-Bolus in Patients With Poorly Controlled Type 2 Diabetes and Very High HbA1c ≥9–15%: DUAL HIGH Trial

Abstract: OBJECTIVE In participants with type 2 diabetes (T2D) and HbA1c >9.0–10.0%, guidelines recommend treatment with basal-bolus insulin. RESEARCH DESIGN AND METHODS This randomized trial compared the efficacy and safety of insulin degludec and liraglutide (IDegLira) and basal-bolus among participants with high HbA1c ≥9.0–15.0%, previously treated with 2 or 3 oral agents and/or basal insulin, allocated (1:1) to basal-bolus (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, IDegLira is also economically advantageous up to a dosage of 25 units compared with the BB combination 30 . Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%‐15%) 31 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the CONCLUDE trial reported no significant difference in the rate of overall symptomatic hypoglycaemia with IDeg-200 vs Gla-300 and nominally lower rates of nocturnal symptomatic and severe hypoglycaemia with IDeg-200 vs Gla-300 [ 79 ]. Compared to the basal-bolus regimen, FRC of IDeg and liraglutide (IDegLira) in PwT2D and HbA 1c ≥ 9.0–15.0% led to a similar reduction in HbA 1c and less hypoglycaemia and weight gain compared with the basal-bolus regimen [ 80 ]. The findings from DELIVER-High Risk study showed that participants on Gla-300 had numerically lower incidences and event rates for all hypoglycaemia and mainly significantly lower incidences and event rates for hypoglycaemia associated with inpatient/ED contacts compared to Gla-100 or IDet [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“… 24 97 For people with marked hyperglycaemia (eg, HbA 1c >10% or with symptoms), clinicians should start insulin, or a combination of insulin with GLP1RAs. 98 When improved glycaemic control is achieved, many people with type 2 diabetes can be safely transitioned to non-insulin treatments with close monitoring to prevent hypoglycemia and hyperglycemia.…”
Section: Drug Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…Basal bolus insulin treatment requires more injections, more glucose testing, more education, and carries a higher risk of hypoglycaemia and weight gain. 98 Metformin or complication centric drugs (GLP1RAs and SGLT2is), or both, should be continued. Sulfonylureas should be discontinued because of the risk of hypoglycaemia with concurrent insulin treatment.…”
Section: Starting and Titrating Insulin Treatmentmentioning
confidence: 99%